Comparison of Clinical Balance and Visual Dependence Tests in Patients With Chronic Dizziness With and Without Persistent Postural-Perceptual Dizziness: A Cross-Sectional Study - De Vestel, Charlotte; De Hertogh, Willem; Van Rompaey, Vincent; Vereeck, Luc (Frontiers in Neurology, 2022)
Background: The diagnosis of persistent postural-perceptual dizziness (PPPD) is primarily based on medical history taking. Research on the value of clinical balance and visual dependence tests in identifying PPPD is scarce. Objectives: (1) to contrast clinical balance and visual dependence tests between PPPD patients, dizzy non-PPPD patients, and healthy persons; and (2) to evaluate whether these clinical tests can help to identify PPPD in patients with chronic dizziness. Methods: Consecutive patients with chronic dizziness (38 PPPD and 21 non-PPPD) and 69 healthy persons underwent Static Balance tests, the Timed Up and Go test, the Tandem Gait test, and the Functional Gait Assessment (FGA). Visual dependence tests included the Visual Vertigo Analogue Scale (VVAS), the Rod-and-Disc test (RDT), and postural sway while facing rotating dots. Groups were compared using ANOVA with post-hoc Tukey, or independent samples t-tests. The value of the clinical tests for PPPD identification was evaluated through logistic regression and Partial Least Squares Discriminant (PLS-DA) analyses. Results: PPPD patients had significantly higher VVAS scores than dizzy non-PPPD patients (p=0.006). Facing rotating dots, PPPD and dizzy non-PPPD patients had increased postural sway compared to healthy persons (PPPD versus healthy: center of pressure (COP) velocity p<0.001, and COP area p<0.001; but non-PPPD versus healthy: COP velocity p=0.116 and COP area p=0.207). PPPD patients had no significantly increased postural sway compared to dizzy non-PPPD patients. PPPD and dizzy non-PPPD patients also scored significantly worse on balance tests compared to healthy persons (PPPD versus healthy: for all balance tests p<0.001; non-PPPD versus healthy: FGA p<0.001, for all other tests p<0.05). Differences were insignificant in balance scores between PPPD and dizzy non-PPPD patients, or in RDT scores between the three study groups. In patients with chronic dizziness, a higher VVAS score was most associated with PPPD (odds ratio 1.04; 95% CI [1.01; 1.07]; p=0.010). The cross-validated (CV) PLS-DA model with all clinical tests included, had fair discriminative ability (CVerror = 47%). Conclusion: PPPD patients were more visually dependent, but did not have worse postural balance compared to dizzy non-PPPD patients. Elevated VVAS scores characterized PPPD most in patients with chronic dizziness.